DEVELOPMENT OF A MOBILE APPLICATION PROTOTYPE (ADHERENCE TRACKER) TO IMPROVE ANTIRETROVIRAL (ARV) MEDICATION ADHERENCE AMONG PEOPLE LIVING WITH HIV/AIDS (PLWHA) IN SURABAYA - Eko Budi Santoso (Bajang Institute, 2025)
Adherence to Antiretroviral (ARV) therapy remains a major challenge for People Living with HIV/AIDS (PLWHA) in Surabaya. This study aims to develop and analyze a mobile application prototype called Adherence Tracker as an effort to enhance adherence to ARV treatment. Employing a qualitative case study approach, data were collected through interviews, observations, and documentation involving PLWHA and healthcare professionals. The findings reveal that the application significantly improves medication consistency through reminder features, automated recording, and personalized motivational messages. Data analysis using the Miles and Huberman model indicated an increase in adherence levels to over 85%. In conclusion, Adherence Tracker proves effective as a user-centered technological innovation to strengthen ARV therapy management and support reproductive health resilience among PLWHA.